QARDUL HASAN AND COMMUNITY EMPOWERMENT: LESSONS CAN BE LEARNED FROM THE TWO BEST PRACTICE LEADING COUNTRIES, INDONESIA AND MALAYSIA - Ziaulrahman Mushkalamzai; Mohammad Wasim Hanif; Azizulrahman Aziz (Al-Amwal : Journal of Islamic Economic Law, 2023)
In Islamic Sharia, Qardul Hasan is a significant tradition of benevolent loans. In the Quran and Sunna, Allah and his messenger Mohammad maintain on giving Qardul Hasan. Some Islamic countries such as Indonesia and Malaysia have worked hard in recent years to use Qardul Hasan based on the principle of benefits to empower the community. However, according to Islamic Sharia, it is still Tabarru. To Use Qardul effectively and empower community, it is needed for it to manage and institutionalize. In Afghanistan, Qardul Hasan is still used classically and it has not been used in the principle of benefits for the development and empowerment of society. As a result, the purpose of this article is to propose a new model of Institutionalization Qardul Hasan for using it based on the principle of benefits to empower and alleviate poverty in Afghan society. This article conducted qualitative research that first examines Qardul Hasan from the perspective of Islamic Sharia. Second, for the practice of the theory some institutions from two leading countries such as Indonesia and Malaysia have been studied.